Elliptic flow of electrons from heavy-flavour hadron decays at mid-rapidity in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Danisch, Meike; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2016)
The elliptic flow of electrons from heavy-flavour hadron decays at mid-rapidity (|y| < 0.7) is measured in Pb-Pb collisions at sNN=2.76$$ \sqrt{s_{NN}}=2.76 $$TeV with ALICE at the LHC. The particle azimuthal distribution with respect to the reaction plane can be parametrized with a Fourier expansion, where the second coefficient (v2) represents the elliptic flow. The v2 coefficient of inclusive electrons is measured in three centrality classes (0-10%, 10-20% and 20-40%) with the event plane and the scalar product methods in the transverse momentum (pT) intervals 0.5-13 GeV/c and 0.5-8 GeV/c, respectively. After subtracting the background, mainly from photon conversions and Dalitz decays of neutral mesons, a positive v2 of electrons from heavy-flavour hadron decays is observed in all centrality classes, with a maximum significance of 5.9σ in the interval 2 < pT < 2.5 GeV/c in semi-central collisions (20-40%). The value of v2 decreases towards more central collisions at low and intermediate pT (0.5 < pT < 3 GeV/c). The v2 of electrons from heavy-flavour hadron decays at mid-rapidity is found to be similar to the one of muons from heavy-flavour hadron decays at forward rapidity (2.5 < y < 4). The results are described within uncertainties by model calculations including substantial elastic interactions of heavy quarks with an expanding strongly-interacting medium.